Advertisement Remove all ads

Show that: cos^(-1)(4/5)+cos^(-1)(12/13)=cos^(-1)(33/65) - Mathematics and Statistics

Sum

Show that:

`cos^(-1)(4/5)+cos^(-1)(12/13)=cos^(-1)(33/65)`

Advertisement Remove all ads

Solution

Let a = `"cos"^-1 (4/5)` and b = `"cos"^-1 (12/13)`

Let a = `"cos"^-1 (4/5)`

cos a = `4/5`

We know that

sin2a = 1 - cos2


sin a = `sqrt (1-"cos"^2 "a")`


`= sqrt (1 - (4/5)^2) = sqrt (1 - 16/25)`


`= sqrt ((25-16)/25) = sqrt (9/25) = 3/5`


Let b = `"cos"^-1 (12/13)`

cos b = `12/13`

W know that

sin2b = 1 - cos2


sin b = `sqrt (1 - "cos"^2 "b")`


`= sqrt (1 - (12/13)^2) = sqrt (1 - 144/169)`


`= sqrt ((169-144)/169) = sqrt (25/169) = 5/13`

We know that 

cos (a+b) = cos a cos b - sin a sin b

Putting values 

cos a = `4/5` , sin a = `3/5`

& cos b = `12/13` , sin b = `5/13`

 

cos (a+b) = `4/5 xx 12/13 xx 3/5 xx 5/13`


`= 48/65 - 3/13`


`= (48 - 15)/65`


`= 33/65`

∴ cos (a+b) = `33/65`

a + b = cos-1 `(33/65)`

`"cos"^-1 4/5 + "cos"^-1 (12/15) = "cos"^-1 (33/65)`

Hence LH.S = R.H.S

Hence proved.

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×